(untitled) (Annals of Medical Research, 2023)
Aim: In this single-center, retrospective study, we aimed to evaluate the effect of CD34+ stem cell dose on hematologic recovery and long-term outcomes such as progression-free survival and overall survival after autologous stem cell transplantation (ASCT). Materials and Methods: In this study, 282 patients with MM, who underwent ASCT between January 2014 and October 2021 were evaluated. The patients were divided into 2 groups according to the infused cell dose. Patients who received ≤5x106/kg CD34+ cells were defined as group A. Patients who received >5x106/kg CD34+ cells were group B. The outcome of ASCT including the time of neutrophil/platelet engraftment, febrile neutropenia status, transplant-related mortality (TRM) at 100 days, duration of hospitalization and survival status were examined in both groups. Results: There were 118 (41.8%) patients in group A and 164 patients (58.2%) in group B. The median neutrophil engraftment was 12 (7-26) days in A group, 11 (6-28) days in B group. The median platelet engraftment was 12 (6-40) and 11 (6-29) days in group B. There were statically significant different in both group for neutrophil and platelet engraftment time (p=.001 and .002, respectively). The median hospitalization time was 16 (10-53) days and 15 (6-83) days in group A and B, respectively. The hospitalization time was statistically significantly different in two groups (p<.012). The mean OS was 53.1±4.2 months in group A and 58.2±3.5 in group B which was not statistically significant difference (p=.841). The mean PFS was 11.8±1.3 months in group A and 19.1±1.4 months in group B which was statistically significant difference in 2 groups (p<0.001). Conclusion: Infusion of >5x106/kg CD34+ stem cells (median dose 9,6 x106/kg) may have a favorable effect on short-term outcomes of transplantation, including short-term neutrophil engraftment, short-term platelet engraftment, and short-term hospitalization. Additionally, progression-free survival may be positively affected by high dose, but upper limit should be defined by new study.